A Ship's Automatic Maneuvering System Using Optimal Preview Sliding Mode Controller with Adaptation Mechanism. Issue 23 (2016) - Mizuno, Naoki; Saka, Naoki; Katayama, Takuya
Abstract: In this paper, we present an automatic ship's maneuvering system using optimal preview sliding mode controller with adaptation mechanism. In this system, the transient overshoot in conventional sliding mode control is reduced by introducing the optimal preview servo method. Moreover, the model based adaptation mechanism keeps the performance of control system for varying and uncertain ship's dynamics. In order to evaluate the performance of the proposed system, computer simulation and actual sea tests carried out using small training ship Shioji-Maru under various conditions. As a result, we can confirm that the control performance is improved under many experimental conditions by comparing with sliding mode based automatic maneuvering system which has been proposed by the authors.